Tocopherol deficiency reduces sucrose export from salt-stressed potato leaves independently of oxidative stress and symplastic obstruction by callose - Amparo Asensi-Fabado, Maria; Ammon, Alexandra; Sonnewald, Uwe; Munne-Bosch, Sergi; Voll, Lars (Journal of Experimental Botany, 2015)
Tocopherol cyclase, encoded by the gene SUCROSE EXPORT DEFECTIVE1, catalyses the second step in the synthesis of the antioxidant tocopherol. Depletion of SXD1 activity in maize and potato leaves leads to tocopherol deficiency and a 'sugar export block' phenotype that comprises massive starch accumulation and obstruction of plasmodesmata in paraveinal tissue by callose. We grew two transgenic StSXD1:RNAi potato lines with severe tocopherol deficiency under moderate light conditions and subjected them to salt stress. After three weeks of salt exposure, we observed a strongly reduced sugar exudation rate and a lack of starch mobilization in leaves of salt-stressed transgenic plants, but not in wild-type plants. However, callose accumulation in the vasculature declined upon salt stress in all genotypes, indicating that callose plugging of plasmodesmata was not the sole cause of the sugar export block phenotype in tocopherol-deficient leaves. Based on comprehensive gene expression analyses, we propose that enhanced responsiveness of SnRK1 target genes in mesophyll cells and altered redox regulation of phloem loading by SUT1 contribute to the attenuation of sucrose export from salt-stressed SXD:RNAi source leaves. Furthermore, we could not find any indication that elevated oxidative stress may have served as a trigger for the salt-induced carbohydrate phenotype of SXD1: RNAi transgenic plants. In leaves of the SXD1: RNAi plants, sodium accumulation was diminished, while proline accumulation and pools of soluble antioxidants were increased. As supported by phytohormone contents, these differences seem to increase longevity and prevent senescence of SXD: RNAi leaves under salt stress.
Keywords: Oxidative stress; potato; salt stress; SnRK1 signalling; starch accumulation; sucrose export defective; tocopherol; tuber yield